Early change in thermal perception is not a driver of anticipatory exercise pacing in the heat. Issue 13 (5th December 2011) - Barwood, Martin James; Corbett, Jo; White, Danny; James, Jason
Abstract : Aim: Initial power output declines significantly during exercise in hot conditions on attaining a rapid increase in skin temperature when exercise commences. It is unclear whether this initial reduced power is mediated consciously, through thermal perceptual cues, or is a subconscious process. The authors tested the hypothesis that improved thermal perception (feeling cooler and more comfortable) in the absence of a change in thermal state (ie, similar deep-body and skin temperatures between spray conditions) would alter pacing and 40 km cycling time trial (TT) performance. Method: Eleven trained participants (mean (SD): age 30 (8.1) years; height 1.78 (0.06) m; mass 76.0 (8.3) kg) completed three 40 km cycling TTs in standardised conditions (32°C, 50% RH) with thermal perception altered prior to exercise by application of cold-receptor-activating menthol spray (MENTHOL SPRAY), in contrast to a separate control spray (CONTROL SPRAY) and no spray control (CON). Thermal perception, perceived exertion, thermal responses and cycling TT performance were measured. Results: MENTHOL SPRAY induced feelings of coolness and improved thermal comfort before and during exercise. Skin temperature profile at the start of exercise was similar between sprays (CON-SPRAY 33.3 (1.1)°C and MENTHOL SPRAY 33.4 (0.4)°C, but different to CON 34.5 (0.5)°C), but there was no difference in the pacing strategy adopted. There was no performance benefit using MENTHOL SPRAY; cycling TT completion time for CON is 71.58 (6.21) min, for CON-SPRAY is 70.94 (6.06) min and for MENTHOL SPRAY is 71.04 (5.47) min. Conclusion: The hypothesis is rejected. Thermal perception is not a primary driver of early pacing during 40 km cycling TT in hot conditions in trained participants.